The Disclosure Obligation of Sustainability Reports In The Banking Sector In Indonesia: A Descriptive Analysis - Rudy Hartanto; Irena Paramita Pramono; Riyang Mardini; Dwi Rahayu (Syntax Corporation, 2022)
Sustainability reporting is a tool for communicating the company's environmental and social reports. This study was conducted to examine how far the sustainability reports are disclosed by banks in Indonesia. Banking sustainability reports in Indonesia have been required by banking regulations since 2019. The analysis is carried out by looking at the development of banking sustainability reports and also conducting different tests before and after the implementation of mandatory sustainability reporting in banking sector. The results show that banks in Indonesia have started making sustainability reports since 2009. Total banks that disclosed sustainability reports experienced a significant increase in 2019 (22.61%) and decreased in 2020 (14.78%). The results also show that there is no difference in banking disclosures on sustainability reports between before and after obligations, that is 2 years before disclosure obligations (2017-2018) and 2 years after disclosure (2019-2020).